Effect of Osteocyte-Ablation on Inorganic Phosphate Metabolism: Analysis of Bone–Kidney–Gut Axis - Fujii, Osamu; Tatsumi, Sawako; Ogata, Mao; Arakaki, Tomohiro; Sakaguchi, Haruna; Nomura, Kengo; Miyagawa, Atsumi; Ikuta, Kayo; Hanazaki, Ai; Kaneko, Ichiro; Segawa, Hiroko; Miyamoto, Ken-ichi (Frontiers in Endocrinology, 2017)
In response to kidney damage, osteocytes increase the production of several hormones critically involved in mineral metabolism. Recent studies suggest that osteocyte function is altered very early in the course of chronic kidney disease. In the present study, to clarify the role of osteocytes and the canalicular network in mineral homeostasis, we performed four experiments. In Experiment 1, we investigated renal and intestinal Pi handling in osteocyte-less (OCL) model mice (transgenic mice with the dentin matrix protein-1 promoter-driven diphtheria toxin [DT]-receptor that were injected with DT). In Experiment 2, we administered granulocyte colony-stimulating factor to mice to disrupt the osteocyte canalicular network. In Experiment 3, we investigated the role of osteocytes in dietary Pi signaling. In Experiment 4, we analyzed gene expression level fluctuations in the intestine and liver by comparing mice fed a high Pi diet and OCL mice. Together, the findings of these experiments indicate that osteocyte ablation caused rapid renal Pi excretion (P<0.01) before the plasma fibroblast growth factor 23 (FGF23) and parathyroid hormone (PTH) levels increased. At the same time, we observed a rapid suppression of renal Klotho (P<0.01), type II sodium phosphate transporters Npt2a (P<0.01) and Npt2c (P<0.05), and an increase in intestinal Npt2b (P<0.01) protein. In OCL mice, Pi excretion in feces was markedly reduced (P<0.01). Together, these effects of osteocyte ablation are predicted to markedly increase intestinal Pi absorption (P<0.01), thus suggesting that increased intestinal Pi absorption stimulates renal Pi excretion in OCL mice. In addition, the ablation of osteocytes and feeding of a high Pi diet affected FGF15/bile acid metabolism and controlled Npt2b expression. In conclusion, OCL mice exhibited increased renal Pi excretion due to enhanced intestinal Pi absorption. We discuss the role of FGF23-Klotho on renal and intestinal Pi metabolism in OCL mice.